2015
DOI: 10.1152/ajpgi.00017.2015
|View full text |Cite|
|
Sign up to set email alerts
|

Nature of extracellular signal that triggers RhoA/ROCK activation for the basal internal anal sphincter tone in humans

Abstract: The extracellular signal that triggers activation of rho-associated kinase (RhoA/ROCK), the major molecular determinant of basal internal anal sphincter (IAS) smooth muscle tone, is not known. Using human IAS tissues, we identified the presence of the biosynthetic machineries for angiotensin II (ANG II), thromboxane A2 (TXA2), and prostaglandin F2α (PGF2α). These end products of the renin-angiotensin system (RAS) (ANG II) and arachidonic acid (TXA2 and PGF2α) pathways and their effects in human IAS vs. rectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…These reconstructs were shown to have functional and molecular properties similar to the intact IAS and demonstrated that the basal tone is dependent on RhoA/ROCK. Altogether, these data suggest that the sphincteric tone is critically dependent on RhoA/ROCK that may be either constitutively active or involve GPCR activation via autocrine control (6,32). In support of these concepts, recent studies by Drs.…”
mentioning
confidence: 75%
“…These reconstructs were shown to have functional and molecular properties similar to the intact IAS and demonstrated that the basal tone is dependent on RhoA/ROCK. Altogether, these data suggest that the sphincteric tone is critically dependent on RhoA/ROCK that may be either constitutively active or involve GPCR activation via autocrine control (6,32). In support of these concepts, recent studies by Drs.…”
mentioning
confidence: 75%
“…The SMs that form the sphincters (tonic SMs) have a unique contractile mechanism resulting in a higher basal tone compared with phasic SMs. It is well established that the major molecular determinant of basal tone in sphincteric GI SMs, such as internal anal sphincter (IAS), is a RhoA-associated kinase (RhoA)/Rho kinase (ROCK) pathway within the specialized SMCs (105)(106)(107)(108).…”
Section: Phenotypic Plasticity Of Gi Smooth Musclementioning
confidence: 99%
“…Ang II effects are mediated by specific receptors, the Ang II type 1 (AT 1 ) and the Ang II type 2 (AT 2 ) receptors, both members of the G-protein-coupled receptor family (De Gasparo et al 2000, Jackson 2001. The presence of Ang II receptors and the other RAS components at various levels along the GI tract has been found in animal preparations , De Godoy et al 2004, De Godoy & Rattan 2005, Wang et al 2005, Ewert et al 2006, Mastropaolo et al 2013a) and also in humans (Hirasawa et al 2002, Ewert et al 2006, Casselbrant et al 2007, Spak et al 2008, Rattan et al 2015, suggesting their potential physiological action. Indeed, some studies have shown that Ang II induces contractile responses either indirectly, via activation of neural AT 1 receptors, or directly, via activation of AT 1 receptors located on smooth muscle cells in different GI tracts of various species, including humans (Hawcock & Barnes 1993, Ewert et al 2006, Casselbrant et al 2007, Spak et al 2008).…”
mentioning
confidence: 97%
“…, Rattan et al . ), suggesting their potential physiological action. Indeed, some studies have shown that Ang II induces contractile responses either indirectly, via activation of neural AT 1 receptors, or directly, via activation of AT 1 receptors located on smooth muscle cells in different GI tracts of various species, including humans (Hawcock & Barnes , Ewert et al .…”
mentioning
confidence: 99%